Spinning Wheel Media in Increasing Knowledge and Attitudes on the Maturity of Marriage Age - Destariyani, Elvi; Yuniarti, Yuniarti; Puspita, Erlin; Nurhayati, Nurhayati (Sarana Ilmu Indonesia (salnesia), 2025)
Indonesia ranked eighth in the number of child marriages, with a total of 25.53 million cases. Bengkulu Province ranked sixth nationally and was the highest in Sumatra Island for child marriages among adolescents aged 10–14 years, with a prevalence of 14,33%. This study aimed to analyze the effectiveness of spinning wheel media in improving knowledge and attitudes regarding the maturity of marriage age (PUP) among adolescents in Bengkulu City. The research employed a quantitative approach with a quasi-experimental design, using a one-group pretest-posttest format. The sample consisted of 60 adolescents from SMPN 17 and SMPN 22 in Bengkulu City. Based on data analysis, after the implementation of the spinning wheel media, adolescents’ knowledge scores ranged from a minimum of 10 to a maximum of 15. The average knowledge score increased to 12,98 after the intervention. A positive change in attitudes was also observed, with a post-intervention average attitude score of 52. The spinning wheel media proved effective in increasing knowledge and promoting positive attitudes toward the maturity of marriage age. It can be utilized as an alternative educational tool in efforts to prevent child marriage.